2006
DOI: 10.1136/oem.2006.028761
|View full text |Cite
|
Sign up to set email alerts
|

Dose–effect relationships between manganese exposure and neurological, neuropsychological and pulmonary function in confined space bridge welders

Abstract: Background: Although adverse neuropsychological and neurological health effects are well known among workers with high manganese (Mn) exposures in mining, ore-processing and ferroalloy production, the risks among welders with lower exposures are less well understood. Methods: Confined space welding in construction of a new span of the San Francisco-Oakland Bay Bridge without adequate protection was studied using a multidisciplinary method to identify the dose-effect relationship between adverse health effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
196
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(208 citation statements)
references
References 32 publications
10
196
1
1
Order By: Relevance
“…Increased concentrations of MnB have been frequently observed in exposed vs non-exposed workers, for example in welders 21 and in smelter workers. 25,26 We determined about 10 mg/l as median MnB in German welders that was similar to the average concentration reported for US welders in bridge building 27 but lower than in Korean welders (15.5 mg/l). 28 A lower average concentration of 8.6 mg/l in Russian welders might be explained by a longer time lag between shift exposure and blood sampling.…”
Section: Discussionsupporting
confidence: 80%
“…Increased concentrations of MnB have been frequently observed in exposed vs non-exposed workers, for example in welders 21 and in smelter workers. 25,26 We determined about 10 mg/l as median MnB in German welders that was similar to the average concentration reported for US welders in bridge building 27 but lower than in Korean welders (15.5 mg/l). 28 A lower average concentration of 8.6 mg/l in Russian welders might be explained by a longer time lag between shift exposure and blood sampling.…”
Section: Discussionsupporting
confidence: 80%
“…Bouchard et al (9) conducted a followup study of alloy workers and concluded that Mn cumulative exposure could lead to learning and memory defi cits. In spite of the criticism due to certain biases pointed out in the above mentioned reports, the fact remains that Bowler et al (8) confi rmed the correlation between abnormal neuropsychological fi ndings and Mn exposure in welders in a dose-related manner.…”
mentioning
confidence: 92%
“…Mergler et al (1999) found a correlation between blood manganese and coordinated movements, learning, and recall. Bowler et al (2007) found a correlation between blood manganese and measures of executive function, memory, sustained concentration and sequencing, verbal learning, cognitive flexibility, visuospatial constructional ability, and visual contrast sensitivity.…”
Section: Does Human Behavioral Neurotoxicology Research Address Riskmentioning
confidence: 99%
“…Park et al (2006) found an association between exposure and the Rey-Osterrieth Complex Figure task, a working memory Index, Stroop Color Word, and Auditory Consonant Trigrams. Bowler et al (2007) later reported a correlation between exposure and tests of executive function, memory, sustained concentration and sequencing, verbal learning in the same population.…”
Section: Does Human Behavioral Neurotoxicology Research Address Riskmentioning
confidence: 99%